Penguatan Kapasitas Pengelolaan Keuangan Badan Usaha pada Status Perguruan Tinggi Negeri Berbadan Hukum - Khoiru Rusydi; Bogat Agus Riyono; Areta Widya Kusumadewi; Wahyu Kartika Larasati; Safira Gusti Deylinda (P3M Politeknik Negeri Malang, 2023)
This social service is held in a workshop with the aim of increasing education and strengthening the financial management capacity of business entities at Brawijaya University with the status of a Legal Entity State University. The social service is carried out with the target of financial staff and business unit stakeholders under the Business Management Agency with a workshop location at UB's Guest House. The research method uses case study research by collecting data from observations through focus group discussions, interviews and documentation. using quantitative analysis based on data interpretation by delivering information in the form of texts and narratives. The results obtained, there are several things that need to be considered in financial management on PTN-BH status, such as changes in regulations, technical reporting and imposition as local taxpayers in several business units.